Local Community Consumption Patterns: The Influence of Social and Economic Conditions on Regional Development - Istiqomah Ni’matul; Hasyim Ibnu Abbas Muhammad; Ema Malinda Manal (E3S Web of Conferences)
Consumption patterns are a picture of information about the amount, type, and frequency of food consumed by community groups. This research aims to discover how society’s social and economic conditions influence consumption patterns in regional development. This type of research is quantitative descriptive research. The population in this study was 192 families in Krajan Hamlet, Kalisat Pasuruan Village, with samples taken based on the Slovin formula of 130. The simultaneous effect in this study was 16.8%. This influence tends to be small because other factors influence people’s consumption patterns apart from social and economic conditions. Other influencing factors are income, level of knowledge, food availability factors, and socio-cultural factors. Income has an essential role in influencing people’s consumption patterns. The higher the income, the more people’s consumption patterns will increase. The level of knowledge increases people’s consumption patterns because people are aware of nutritional patterns. Meanwhile, socio-cultural factors have a role in influencing consumption patterns because the traditional environment also has a role in influencing a person’s consumption patterns. Recommendations for further research include choosing variables other than social and economic factors influencing family consumption patterns.